Green Marketing Marketing Strategy to Attract Consumers who Care about the Environment - Popo Suryana (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2023)
Green marketing is a marketing approach that focuses on environmentally friendly products and services, and places emphasis on sustainable values. Consumers who are increasingly concerned about environmental issues are the main target in implementing this strategy. This research aims to explore and analyze the effectiveness of green marketing strategies in attracting consumers who care about the environment. This research uses a qualitative approach with descriptive methods. The research results show that green marketing strategies have a positive impact in attracting consumers who care about the environment. A thorough analysis of the implementation of green marketing strategies by successful companies shows that information transparency, collaboration with environmental organizations and educational campaigns are key factors influencing the effectiveness of these strategies. Companies that consistently provide detailed information about product composition, production methods and environmental impacts are successful in building credibility and consumer trust. Collaboration with leading environmental organizations has also proven to be a strategic step to access consumer markets that are more sensitive to environmental issues. Educational campaigns that successfully communicate the benefits of sustainable products and encourage customer participation in environmental efforts have also proven effective in increasing awareness and improving customer relationships.